Operational conflict management process between military peacekeepers and humanitarian NGOS in West Africa (2014)
The face of peacekeeping activities across the globe has changed from traditional into wider peacekeeping since the end of the cold war. Hitherto, the task of peacemaking and peacekeeping was considered a purview of the military because of the complex task involved in persuading belligerent armed groups to lay down arms for peaceful negotiation to take place. Thus, during the cold war era, the activities of the United Nations Peacekeepers loomed largely in conflict zones across the world. However, there has been a remarkable increase in the involvement of regional organisations in spearheading peacekeeping and peace enforcement with mandates and support from the UN. There has also been a remarkable increase in the participation of non-state voluntary groups and organisations who contribute to relief activities and peace-building efforts in conflict zones as complements to military operations to mitigate the effects of armed conflicts